Determination of Total Flavonoid Content of Red Fruit Juice (Pandanus conoideus Lam) by a UV–Vis Spectrophotometer - Sulaeman, Nur Rachmi; Pratama, Mamat; Kusuma, Andi Trihadi (Universitas Muslim Indonesia, 2025)
Red fruit (Pandanus conoideus Lam) belongs to the pandanacea family. This plant contains compounds such as tannins, flavonoids, steroids, triterpenoids and alkaloids and has properties in curing various diseases such as diabetes, coronary heart disease, hypertension, cancer and HIV/AIDS. This study aims to determine the total flavonoid content of red fruit juice (Pandanus conoideus Lam) using a UV - Vis spectrophotometer. The stages carried out in this research began with sample preparation, qualitative testing of flavonoid compounds and determining the total flavonoid content of red fruit (Pandanus conoideus Lam) samples. The results obtained in this study based on a qualitative test using NaOH reagent stated that red fruit juice (Pandanus conoideus Lam) was positive for containing flavonoids and in a quantitative test using a UV - Vis spectrophotometer the percent concentration obtained in the red fruit juice sample was 8.7258%.